Moisture buffer potential of experimental wall assemblies incorporating formulated hemp-lime. (November 2015) - Latif, Eshrar; Lawrence, Mike; Shea, Andy; Walker, Pete
Abstract: Experiments were carried out according to the Nordtest protocol to study the moisture buffer potential of hemp-lime walls with a range of different internal linings and surface treatments. It was observed that the moisture buffer value was 'Excellent' when the inner surface of hemp-lime was exposed. 'Excellent' moisture buffer values were also obtained for hemp-lime with lime plaster. All other assemblies demonstrated 'Good' moisture buffer value. Moisture buffer values of the assemblies, after application of paint on the upper surfaces, were also determined. It was observed that application of synthetic pigment based trade paint could reduce the moisture buffer performance of the assembly consisting of hemp-lime and lime-plaster from 'Excellent' to 'Good' while between 61 and 69% reduction of moisture buffer value was observed for the other assemblies. However, the reduced buffer values of the assemblies are still comparable with other moisture buffering building materials. It was further observed that moisture buffer performance was improved when clay based organic paint was used instead of trade paint. Highlights: Moisture buffer values (MBV) of hemp-lime assemblies were determined. Use of inner linings decreases the MBV significantly. Decreased values are yet within the range of 'Good' MBV. Hemp-lime shows better MBV with clay based paint than with the trade one.